Hypocapnia Stimuli-Responsive Engineered Exosomes Delivering miR-218 Facilitate Sciatic Nerve Regeneration - Wang, Yingshuai; Yu, Tao; Hu, Feihu (Frontiers in Bioengineering and Biotechnology, 2022)
Therapeutic strategies of microRNAs (miRNAs) and exosomes have been systematically explored as enhancing application by paracrine and modulation cellular activity after internalization of recipient cells in vitro, and progressively developed to meet the requirements of peripheral nerve regeneration in vivo. However, how to obtain exosomes with superior properties and effectively deliver miRNAs becomes a key challenging. Hypocapnia environment might play unexpected outcomes in strengthening exosomes function when culturing adipose-derived stem cells (ASCs). Previously, we discovered the intensive regulation of miR-218 on the differentiation of ASCs. In the present study, we analyzed the functional differences of secreted exosomes in response to hypocapnia stimulation, and explored the application in combination with miR-218 to facilitate sciatic nerve regeneration. Our results indicated that the delivery system of engineered exosomes derived from ASCs remarkably loads up-regulated miR-218 and promotes cellular activity in the recipient cells (PC12 cells), and hypocapnia stimuli-responsive exosomes exhibit strengthening properties. Furthermore, in a sciatic nerve injury model, exosomes delivering miR-218 combined with engineered scaffold facilitated the regeneration of injured sciatic nerves. In the hypocapnia stimulated exosomes group, more encouraging promotion was revealed on the regeneration of motor and nerve fibres. Hypoc-miR-218-ASCs exosomes is suggested as a promising cell-free strategy for peripheral nerve repair.